CIZ1 in Xist seeded assemblies at the inactive X chromosome - Sofi, Sajad; Coverley, Dawn (Frontiers in Cell and Developmental Biology, 2023)
There is growing evidence that X-chromosome inactivation is driven by phase-separated supramolecular assemblies. However, among the many proteins recruited to the inactive X chromosome by Xist long non-coding RNA, so far only a minority (CIZ1, CELF1, SPEN, TDP-43, MATR3, PTBP1, PCGF5) have been shown to form Xist-seeded protein assemblies, and of these most have not been analyzed in detail. With focus on CIZ1, here we describe 1) the contribution of intrinsically disordered regions in RNA-dependent protein assembly formation at the inactive X chromosome, and 2) enrichment, distribution, and function of proteins within Xist-seeded assemblies.